The Hondbook Le Drogman Turc By A. Chodzko and his importanec as Linguistic Source
Beşinci Milletlerarası Türkoloji Kongresi, İstanbul, 23-28 Eylül 1985, Tebliğler, Türk Edebiyatı İstanbul 1985, 187- 191 ss.